Jude The Obscure - Hardy, Thomas (London Pan1974, 1974)
This is the story of a young country workman obsessed by his ambition to become an Oxford student, interwoven with his fraught relationships with two women.
Keywords: England--Wessex -- Stonemasons -- Adultery